Rent-seeking competition from State coffers : a calibrated DSGE model of the Euro area - Konstantinos Angelopoulos; Apostolis Philippopoulos; Vanghelis Vassilatos (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper incorporates an uncoordinated struggle for extra fiscal favors into an otherwise standard Dynamic Stochastic General Equilibrium model. This reflects the popular belief that interest groups compete for privileged transfers and tax treatment at the expense of the general public interest, and so the aggregate economy stagnates. The model is calibrated to the euro area over the period 1980-2003. Our results show that rent-seeking competition can contribute to explaining the European macroeconomic experience. We also get quantitative evidence of the fraction of collected tax revenues grabbed by rent seekers.
Keywords: H23; E62; E32; 330; rent seeking; fiscal policy; real business cycles; Rent Seeking; Finanzpolitik; Real Business Cycle; Allgemeines Gleichgewicht; Theorie; EU-Staaten